The Relationship Between Body Image, Eating Behavior, and Physical Activity on the Nutritional Status of Adolescents Among Medical Students - Ronauli Batubara, Frisca; Aji Patriawati, Keswari; Vilanda Sisthaningrum, Ni Made Evina (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescence is a crucial period of physical and psychological development, often accompanied by dissatisfaction with body image. Many adolescents struggle to accept their body shape, which can influence eating behavior and physical activity, ultimately affecting nutritional status. Objective: This study aimed to determine the relationship between body image, eating behavior, and physical activity on the nutritional status of adolescents. Method: A cross-sectional study was conducted among 115 medical students from the Faculty of Medicine, Christian University of Indonesia, Class of 2018. Data were collected through online questionnaires, including the Body Shape Questionnaire-34, Eating Attitude Test-26, and International Physical Activity Questionnaire. The data were analyzed using the chi-square test. Result and Discussion: The analysis showed that eating behavior had the most significant influence on nutritional status, with a p-value of 0.035. This finding indicates that irregular eating patterns and excessive dietary control may contribute to imbalanced nutrition among adolescents. Conclusion: There is a significant relationship between eating behavior and nutritional status among adolescents. Promoting healthy eating habits and positive body perception is essential to maintain optimal nutritional health during adolescence.